Respuesta :
First, rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation : 3*(2*x-1)-(4*x+2)=0
= 3 * (2x - 1) - (4x + 2) = 0
= 2x - 5 = 0
= 2x-5 = 0 ---- Add 5 to both sides of the equation --->
= 2x = 5
Then you will divide both sides of the equation by 2 and get,
= x = 5/2 OR 2.5
I hope this helps!
= 3 * (2x - 1) - (4x + 2) = 0
= 2x - 5 = 0
= 2x-5 = 0 ---- Add 5 to both sides of the equation --->
= 2x = 5
Then you will divide both sides of the equation by 2 and get,
= x = 5/2 OR 2.5
I hope this helps!